Peranan Media Sosial Instagram untuk Meningkatkan Citra Merek Dojang Taekwondo Dns Semarang - Kikan Nurhaliza Raniku; Febrianur Ibnu Fitroh Sukono Putra; Sisca Dian Rahmawati (BUSMI : Journal of Business and Management Innovations, 2025)
Marketing management is a crucial aspect in achieving the marketing goals of a product or service, including in the context of sports such as taekwondo. This study focuses on the role of social media, especially Instagram, in enhancing the brand image and membership of Dojang Taekwondo DnS in Semarang. Established in 2012, Dojang DnS faces challenges in promoting its club, which currently relies on word-of-mouth marketing strategies. Through qualitative data analysis and social media, this study found that elements such as attractive profiles, quality content, active interactions, and the use of relevant hashtags can significantly increase audience engagement. The obstacles faced include lack of account visibility and difficulty in attracting audience attention. The results of this study indicate that the use of social media can strengthen relationships with the community and contribute to membership growth, while highlighting the importance of a more planned and structured marketing strategy in promoting Dojang taekwondo activities.